The Effect of Using the Duolingo Application in Enriching High School Students’ Vocabulary Mastery - Romanda, Shobratul; Dahmilsyah; Daud, Afrianto (IKIP Siliwangi, 2025)
This research aims to find out the effect of using the Duolingo Application in enriching high school students’ vocabulary mastery. The participants of this research were the eleventh grade at one private school in Riau province in the academic year 2024/2025. Using a pre-experimental method with a one-shot study case design. Sampling in this method uses a purposive simple, so this study involved a sample of 25 students who underwent treatment and a vocabulary test after using the Duolingo application. The results showed a significant increase in students' vocabulary mastery, with the average score increasing from 54.32 (pre-test) to 72.2 (post-test). Statistical analysis using a paired sample t-test showed a significance value of <0.001, which confirmed the positive effect of the Duolingo app on vocabulary acquisition. This study highlights the Duolingo app as an effective digital tool to encourage vocabulary development, offering teachers and students a modern and interactive learning platform. Recommendations are given to integrate the app into classroom teaching to improve language learning outcomes.